2009
DOI: 10.1002/jbm.a.32518
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative behavior of biomineral/agarose composite gels as bone grafting materials in rat cranial defects

Abstract: The main objective of this study was to evaluate the biological behavior of Hydroxyapatite (HAp)/agarose and calcium carbonate (CaCO3)/agarose composite gels by an alternate soaking process used for the treatment of surgically produced bone defects in rat cranium. We designed the following four groups: (i) HAp (HAp/agarose composite gel), (ii) CaCO3 (CaCO3/agarose composite gel), (iii) Agarose (bare agarose gel), and (iv) Defect (no filling materials). We subdivided (i) (ii) (iii) into two application types as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 31 publications
(48 reference statements)
0
36
0
Order By: Relevance
“…Both apatite and calcium carbonate are reported to show high biological compatibility in vivo 25,26) . The results in the present study indicate the possibility of designing organicinorganic hybrids with different mechanical properties, bioresorbability and biological response for dental and orthopaedic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Both apatite and calcium carbonate are reported to show high biological compatibility in vivo 25,26) . The results in the present study indicate the possibility of designing organicinorganic hybrids with different mechanical properties, bioresorbability and biological response for dental and orthopaedic applications.…”
Section: Discussionmentioning
confidence: 99%
“…When either HA/agarose or CaCO 3 /agarose were implanted in rat cranial bone defects, we found that the defects were subsequently filled with newly formed bone [11]. Eight weeks after implantation, dual energy X-ray absorptiometry (DEXA) and peripheral quantitative computed tomography (pQCT) analysis showed that there was no significant difference in the volume of newly formed bone in defects implanted with either HA/agarose or CaCO 3 /agarose.…”
Section: Introductionmentioning
confidence: 99%
“…1). Moreover, we were unable to detect HAp particles or agarose at the site by histological examination, because HAp gel contains nanoparticles of HAp in and on the organic polymer matrix [4,5,7]. Defects of any shape can easily be filled with HAp gel because of the high plasticity of the graft material.…”
Section: Discussionmentioning
confidence: 86%
“…Published by Elsevier Ltd. All rights reserved. ଝ [4][5][6][7][8]. Its ability was enhanced in the presence of mesenchymal stromal cells [8].…”
Section: Introductionmentioning
confidence: 99%